Sense of agency in joint action: a critical review of we-agency - Le Besnerais, Alexis; Moore, James W.; Berberian, Bruno; Grynszpan, Ouriel (Frontiers in Psychology, 2024)
The sense of agency refers to the experience of control over voluntary actions and their effects. There is growing interest in the notion of we-agency, whereby individual sense of agency is supplanted by a collective agentic experience. The existence of this unique agentic state would have profound implications for human responsibility, and, as such, warrants further scrutiny. In this paper, we review the concept of we-agency and examine whether evidence supports it. We argue that this concept entails multiplying hypothetical agentic states associated with joint action, thus ending up with an entangled phenomenology that appears somewhat speculative when weighted against the available evidence. In light of this, we 2 suggest that the concept of we-agency should be abandoned in favour of a more parsimonious framework for the sense of agency in joint action.